A refrigeration system for the temperature calibration - HUDDAR, B. B.; JADHAV, B. G. (MAUSAM, 1964)
The paper describes a deep freeze. refrigeration system constructed by the authors in the Instruments Division of the Meteorological Office at Poona, and used for the temperature calibration of radiosondes The refrigeration system using Freon 22 and Freon 13 in a cascade operation cools four calibration chambers to, -70 °C in about 1 hr 30 min.